Judge political affiliation and impacts of corporate environmental litigation - Liu, Chelsea (Journal of corporate finance (Amsterdam, Netherlands), 2020)
This study examines the role of judges' political affiliation in determining the outcomes of environmental lawsuits filed against public corporations and their economic impacts on the defendant firms. Drawing on legal theories of judicial decision making, individual judges are expected to play an important role in influencing lawsuit outcomes and consequently the sued firms' shareholder wealth. This study employs a hand-collected sample of environmental lawsuits filed in the U.S. Federal District Courts against public firms during 2000–2015, utilizing the random assignment of judges to lawsuits to combat endogeneity concerns. The empirical evidence shows that lawsuits with Republican-appointed judges are approximately 12% less likely to succeed in reaching a settlement compared with those adjudicated by Democratic-appointed judges, holding constant other lawsuit-, judge-, and firm-specific factors. Further, investors of defendant firms react more favorably to the outcome of a lawsuit adjudicated by a Republican-appointed judge compared with a Democratic appointee: the difference of 0.6% of market value during the three-day period surrounding the lawsuit conclusion represents a substantial saving of shareholder wealth. These significant differences are not attributable to alternative explanations, such as other judge idiosyncrasies or firm characteristics, and remain robust to a series of additional analyses. These empirical findings offer new insights into the significant impacts of judge political affiliation on corporate environmental litigation and provide novel evidence on the magnitude of their economic consequences. •This study examines the role of judges' political affiliation in corporate environmental lawsuits.•Judge political affiliation significantly predicts lawsuit outcomes.•Sued firms experience more positive stock market reactions to lawsuit resolution under Republican judges.•These differences cannot be explained by judge racial backgrounds or other demographic factors.